Self-neglect among older adults with disabilities in Liaoning Province during the COVID-19 outbreak: A cross-sectional study - Dong, Li; Sun, Longfeng (Frontiers in Psychology, 2022)
Background: Self-neglect among older adults is a well-recognized public health issue. During the novel coronavirus disease 2019 (COVID-19), older adults with disabilities may be at increased risk for self-neglect. The aim of this study was to assess the prevalence of self-neglect and associated factors among older adults with disabilities in Liaoning Province during the COVID-19 outbreak. Methods: A cross-sectional study was conducted from January 2021 to April 2021. A convenience sample of 230 older adults with disabilities responded to a questionnaire that collected data on socio-economic and demographic characteristics, alongside data using the Barthel Index (BI), Elder Self-Neglect Assessment (ESNA), Geriatric Depression Scale-Short Form (GDS-SF), Multidimensional Scale of Perceived Social Support (MSPSS), and Mini-Mental State Examination (MMSE). Results: The overall self-neglect rate was 86%. The study revealed that self-neglect correlates positively with the degree of disability (p＜0.001) and depressive symptoms (p＜0.001). Monthly income (p = 0.002) and perceived social support (p = 0.001), in contrast, were negatively associated with self-neglect. Conclusions: During the period of the COVID-19 outbreak, self-neglect is a serious public health problem among older adults with disabilities. Lower monthly income, decreased physical function, depressive symptoms, and perceptions of poor social support were contributing factors for self-neglect among older adults with disabilities.